Tindak Tutur Ekspresif Netizen Pada Pemberitaan Konflik Palestina-Israel di Sosial Media Instagram - Adlina, Adlina; Martutik, Martutik; Susanto, Gatut (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2024)
The purpose of this study was to expland the form of expressive speech and speech strategy by netizens from conflict of Israel-Palestina news on instagram. This type of research is qualitative research using descriptive methods, especially by employing Searle’s theory of speech acts. Data in this reseach were word, phrases, clauses and sentences that represent the form of expressive speech and speech strategy. Based on the results of the study, it was found five types form of expressive speech, namely condolence speech, insinuating speech, angry speech, complaining speech, and humor speech and four types of speech strategy, namely strategy of speaking frankly without preamble, strategy of speaking speaking with positive politeness, strategy of speaking with negative preamble and the strategy speak vaguely. Based on the results of the study, it can be concluded that the the form of expressive speech by netizens from Israel-Palestina news is a stimulus response from the news. The strategy of expressive speech caused by personality, pretension, and speaker purpose. The form of expressive speech determines the expressive speech strategy.